Field Researchers at Camp Finney Wapusk National Park standing along the perimeter of a grass exclosure - Bazely, Dawn (1982)
Field researchers are seen standing at the perimeter of one of the sections of grass that has been sectioned off with wooden stakes,chicken wire, and orange flags. This section of grass is the most concentrated growth area as be seen in the photograph. Behind the field researchers, there is a small body of water